Implementation of the 5R culture in UNY educational staff in the context of continuous improvement - Widyanti, Perdaning; Wulandari, Aprilianti; Triyanto, Triyanto; Yektif, Dama Ilmia Andrian (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2024)
This research aims to examine the implementation of Kaizen culture among educational staff (tendik) at Yogyakarta State University (UNY), as well as the challenges, obstacles and institutional strategies in implementing it. The Kaizen culture studied focuses on the 5R principles (Concise, Neat, Clean, Careful, Routine). This research uses quantitative methods with a descriptive approach, where data is obtained through questionnaires, observations and interviews. The sampling technique used simple random sampling, with a population of 891 UNY educational staff. The research results show that the implementation of Kaizen culture at UNY has gone well, with a total average score of 736.79, which is in the "High" category. The highest score is in the "Concise" dimension (798.5), followed by "Neat" (763), "Care" (745.83), "Clean" (694.33), and "Routine" (683.22) . However, the main challenges and obstacles include a lack of consistency in implementation and awareness of the 5R principles. Proposed strategies to overcome these challenges include more intensive training and ongoing management support. By implementing the 5R culture, UNY creates a more productive and organized work environment, which ultimately contributes to increasing effectiveness and quality of work results.